(untitled) (Jurnal Pustaka, 2025)
The sexual division of labour within households remains a crucial issue in family sociology, especially among urban Batak Toba communities negotiating the tensions between Dalihan Na Tolu cultural values, economic pressures, and HKBP Christian teachings. This study aims to describe the patterns of sexual division of labour among the HKBP Perumnas Simalingkar congregation in Medan and to analyse how biological factors (nature), social construction (nurture), cultural norms, and HKBP contextual theology interact in shaping gender roles. Using a qualitative case study approach, the research employed in-depth interviews and participatory observation with 15 congregation families. The findings reveal a dominant pattern in which women continue to bear the primary domestic workload despite participating in paid employment, resulting in a double burden that is rarely balanced by equal male involvement. Batak cultural norms through Dalihan Na Tolu and literal biblical interpretations reinforce traditional gender roles, yet urbanisation and economic needs create spaces for role negotiation. Unlike previous studies that focused mainly on cultural or economic aspects, this research highlights the contribution of HKBP’s contextual theology as a medium for renegotiating gender norms within an urban Christian community. This study contributes to the discourse on gender, family sociology, and urban studies in Indonesia.